Preparation method of surface hydrophobic modified nano inorganic powder and functional fiber
By forming a hydrophobic layer on the surface of nano-inorganic powder, the problem of poor dispersion in organic polymers is solved, the strength and performance of the fibers are improved, and more uniform dispersion and better application effects are achieved.
Patent Information
- Application Number
- CN202510051862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Nanoinorganic powders are prone to agglomeration due to their large specific surface area and many hydroxyl groups on the surface, resulting in uneven dispersion in organic polymers, affecting the strength and performance of the fibers.
By heating the nano-inorganic powder with boric acid, the surface hydroxyl group is activated, and then reacting with long carbon alkanol to form a hydrophobic layer to improve its dispersion.
It effectively solves the problem of poor dispersion of nano-inorganic powders in organic polymers, improves the strength and performance of fibers, and has a simple process and environmental protection.
Smart Images

Figure CN119751978A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials and relates to a method for preparing surface hydrophobic modified nano inorganic powder and functional fiber. Background Art
[0002] As an important functional material, nano-inorganic powder plays a key role in many fields. In the field of fiber, the application of nano-inorganic powder brings many excellent properties to fiber materials. For example, nano-inorganic powder can improve the strength, wear resistance and corrosion resistance of fiber, and also give fiber special functions such as antibacterial, anti-ultraviolet, heat insulation and warmth. In addition, nano-inorganic powder can also improve the dyeing performance and feel of fiber, making it more comfortable and beautiful.
[0003] However, there are also some problems with the application of nano-inorganic powders, the most prominent of which is the easy agglomeration. This is mainly due to the extremely high specific surface area and surface energy of nano-inorganic powders, which makes the particles attract each other and form agglomerates. The agglomeration of nano-inorganic powders will not only reduce their dispersibility and stability, but also affect their application effect in materials such as fibers, resulting in the inability to spin or the problem of insufficient strength of the produced fibers.
[0004] In order to solve the agglomeration problem of nano-inorganic powders and improve their dispersibility and stability, people have conducted a lot of research and developed a variety of surface modification methods. At present, the commonly used surface modification methods of nano-inorganic powders mainly include surfactant modification, coupling agent modification, polymer coating modification, etc. Although these methods can improve the performance of nano-inorganic powders to a certain extent, they also have some shortcomings. For example, surfactant modification is prone to desorption, resulting in unstable modification effect; coupling agent modification is costly and the process is complicated. It is difficult to control the occurrence of side reactions during the modification process. The surface properties of the modified nano-inorganic powders are greatly affected by the modification conditions, and the surface modification is uneven; polymer coating modification may affect the original properties of the nano-inorganic powders. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing surface hydrophobic modified nano inorganic powder and functional fiber, which is used to solve the agglomeration problem of nano inorganic powder caused by large specific surface area and many surface hydroxyl groups, thereby solving the problem of uneven dispersion and easy agglomeration of nano inorganic powder in organic polymer, so that nano inorganic powder is evenly dispersed in the fiber to improve the comprehensive performance of the composite fiber.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a surface hydrophobic modified nano inorganic powder, comprising the following steps:
[0008] S1: heating the nano inorganic powder and boric acid to react to obtain hydroxyl activated nano inorganic powder;
[0009] S2: reacting the hydroxyl-activated nano-inorganic powder with a long carbon chain alkanol to obtain a surface hydrophobic-modified nano-inorganic powder.
[0010] Furthermore, in step S1, the nano inorganic powder is selected from one or more of nano silicon dioxide, nano titanium dioxide, nano tourmaline, nano zirconium carbide or nano zinc oxide; the particle size of the nano inorganic powder is 10 to 500 nm, and the mass ratio of the nano inorganic powder to boric acid is 5 to 15:1.
[0011] Furthermore, in step S1, in the heating reaction, the reaction temperature is 400-600° C., and the reaction time is 2-5 h.
[0012] Furthermore, in step S2, the molecular formula of the long carbon chain alkanol is CH 3 (CH 2 ) n OH, wherein n=8-14, and the mass ratio of the nano inorganic powder to the long carbon chain alkanol is 1:4-8.
[0013] Furthermore, in step S2, in the reaction, the catalyst is one or more of concentrated sulfuric acid, dodecylbenzenesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid.
[0014] Furthermore, in step S2, in the reaction, the reaction temperature is 70 to 150° C., and the reaction time is 2 to 7 hours.
[0015] The second aspect of the present invention provides a method for preparing a functional fiber, comprising: melt-blending and extruding a surface hydrophobically modified nano inorganic powder, a polymer slice, a dispersant and an antioxidant to obtain a functional masterbatch, and melt-spinning to obtain the functional fiber;
[0016] The surface hydrophobic modified nano inorganic powder is prepared by the method according to any one of claims 1 to 6.
[0017] Further, the polymer slice is selected from one of polyethylene terephthalate (PET) slice, polyamide slice, and polypropylene slice;
[0018] The dispersant is vinyl bisstearamide (EBS) or zinc stearate, and its mass content in the functional masterbatch is 0.3-3%;
[0019] The antioxidant is antioxidant 1010 or antioxidant 1076, and its mass content in the functional masterbatch is 0.01-0.5%;
[0020] The mass content of the surface hydrophobic modified nano inorganic powder in the functional masterbatch is 1-30%.
[0021] Furthermore, the mass content of the surface hydrophobic modified nano inorganic powder in the functional fiber is 1-10%.
[0022] Furthermore, the melt spinning comprises: directly melt spinning the functional masterbatch or mixing it with additional polymer chips and then adding it into a melt spinning machine for spinning.
[0023] The present invention adopts the alcohol ester method for modification. The modification principle is that the hydroxyl groups of the alkanol molecules interact with the active sites on the surface of the nano inorganic powder to form adsorption or chemical bond bonding. The long-chain carbon-hydrogen structure builds a hydrophobic layer on the surface to reduce the surface energy. The advantages are obvious. It can improve the dispersibility of the nano inorganic powder and make it evenly distributed in various media; enhance the compatibility with the organic matrix and improve the fiber quality; the process is simple, easy to operate and control; it is green and environmentally friendly, with low toxicity and little harm; it can also be adjusted as needed to meet different application requirements.
[0024] Compared with the prior art, the present invention has the following characteristics:
[0025] The present invention provides a method, preparation and application of surface hydrophobic modification of nano inorganic powders. First, boric acid is used to activate the surface reaction sites of the nano inorganic powders. Then, a long carbon chain alkanol is used as a surface modifier. Under acid catalysis conditions, the long carbon chain is introduced into the surface of the nano inorganic powders to prepare modified nano inorganic powders. The method has a simple processing process and mild reaction conditions. No toxic organic reagents are used as solvents. At the same time, the modifier can be recycled and reused, which is green and environmentally friendly and in line with sustainable development. The inorganic powders in the functional masterbatch and functional fiber prepared by melt blending are evenly dispersed, which can effectively solve the problems of poor dispersibility and easy agglomeration in organic polymers, so that the fiber strength and performance are less affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is the infrared spectrum of nano silicon dioxide before and after modification of Example 3.
[0027] Figure 2 This is the water contact angle diagram of nano-titanium dioxide before and after modification in Example 7.
[0028] Figure 3 1 is a scanning electron microscope (SEM) image of the nano-tourmaline powder before and after modification of Example 9. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0030] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.
[0031] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0032] The contact angle test steps in the following embodiments are as follows: take an appropriate amount of sample powder and place it in a grinder, press it under a pressure of 10 MPa to prepare a sample, place the prepared sample slice on a glass slide, and then place the glass slide on the sample platform; adjust the platform to keep it level, turn on the light source, and adjust the glass slide on the sample platform to appear in the center of the screen. Use a needle to titrate deionized water (3 μL) on the surface of the sample, and use a CCD camera to take real-time photos to record the morphology of the water droplets and measure the contact angle. Measure 3 times, and the average value of the contact angle calculated is the measured sample contact angle.
[0033] The thermal conductivity test method in the following embodiments is as follows: the thermal conductivity of the composite fiber is tested using a TCi thermal conductivity tester. During the test, the sample is placed on the detection head, and then a 500g weight is placed on the sample. The test is repeated 5 times and the average value is taken.
[0034] The linear density of the fibers in the following examples is measured according to the test method of GB / T 14343-2008.
[0035] The breaking strength and breaking elongation of the fibers in the following examples are measured with reference to the test method of GB / T 14344-2022.
[0036] In the following examples, UPF is measured according to the test method of GB / T 18830-2009.
[0037] The negative oxygen ion test method in the following examples is as follows: The prepared fiber is tested for negative ion performance on an ITC-201A negative ion tester. The fiber is placed about 1 cm away from the tester, and a glass rod is used to rub the fiber surface at a constant speed of about 120 times / min.
[0038] The light heat storage performance in the following embodiments is measured with reference to the GB / T 18319-2019 test method.
[0039] The antibacterial properties in the following examples were measured with reference to the GB / T 20944.1-2008 test standard, using the oscillation method, and evaluated by the plate count method.
[0040] Example 1
[0041] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0042] (1) Weigh 100 g of nano-silicon dioxide powder with a particle size of 10 nm and 20 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 600°C for 2 h. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-silicon dioxide powder.
[0043] (2) Add hydroxyl-activated nano-silica powder and 3 g of p-toluenesulfonic acid to 500 g of tridecanol, stir to fully disperse the nano-silica powder in the tridecanol, then heat to 150° C., react for 2 h, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0044] A polyamide 6 functional fiber, the preparation method of which comprises the following steps:
[0045] (1) 100 g of modified nano-silica powder, 390.5 g of polyamide 6 chips, 7.5 g of EBS and 2 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyamide 6 functional masterbatch with a silica content of 20%.
[0046] (2) A polyamide 6 functional masterbatch with a silica content of 20% is mixed with polyamide 6 chips and melt-spun to produce a polyamide 6 functional fiber with a silica content of 8%.
[0047] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 16°, and the contact angle of the nano-silica sample after modification was measured to be 125°. The obtained polyamide 6 / silica functional fiber with a functional powder content of 8% had a linear density of 58 dtex, a breaking strength of 3.4 cN / dtex, a breaking elongation of 50%, and a thermal conductivity of 0.0402 W / (m·K).
[0048] Example 2
[0049] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0050] (1) Weigh 100 g of nano-silicon dioxide powder with a particle size of 40 nm and 15 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 550° C. for 3 h. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-silicon dioxide powder.
[0051] (2) Add hydroxyl-activated nano-silica powder and 4 g of benzenesulfonic acid to 420 g of octanol, stir to fully disperse the nano-silica powder in the octanol, then heat to 110° C., react for 4 hours, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0052] A polyamide 6 functional fiber, the preparation method of which comprises the following steps:
[0053] (1) 100 g of modified nano-silica powder, 889 g of polyamide 6 chips, 10 g of EBS and 1 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyamide 6 functional masterbatch with a silica content of 10%.
[0054] (2) A polyamide 6 functional masterbatch with a silica content of 10% was mixed with polyamide 6 chips and melt-spun to produce a polyamide 6 functional fiber with a silica content of 5%.
[0055] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 18°, and the contact angle of the nano-silica sample after modification was measured to be 117°. The obtained polyamide 6 / silica functional fiber with a functional powder content of 5% had a linear density of 60 dtex, a breaking strength of 4.9 cN / dtex, an elongation at break of 29%, and a thermal conductivity of 0.0447 W / (m·K).
[0056] Example 3
[0057] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0058] (1) Weigh 300 g of nano-silicon dioxide powder with a particle size of 50 nm and 25 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 500°C for 3.5 hours. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-silicon dioxide powder.
[0059] (2) Add hydroxyl-activated nano-silica powder and 12 g of p-toluenesulfonic acid to 1530 g of tridecanol, stir to fully disperse the nano-silica powder in the tridecanol, then heat to 90° C., react for 5 hours, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0060] like Figure 1 The infrared spectra of nano silicon dioxide before and after modification in Example 3 are shown. 2 is the nano-silicon dioxide powder before modification, curve SiO 2Mod is the infrared spectrum of modified nano-silicon dioxide powder. The horizontal axis is the wave number and the vertical axis is the absorbance. -1 The absorption peaks of methyl and methylene groups can determine whether the surface grafting modification of nano-silica is successful.
[0061] A polyamide 6 functional fiber, the preparation method of which comprises the following steps:
[0062] (1) 300 g of modified nano-silica powder, 665 g of polyamide 6 chips, 30 g of EBS and 5 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyamide 6 functional masterbatch with a silica content of 30%.
[0063] (2) A polyamide 6 functional masterbatch with a silica content of 30% is mixed with polyamide 6 chips and melt-spun to produce a polyamide 6 functional fiber with a silica content of 10%.
[0064] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 16°, and the contact angle of the nano-silica sample after modification was measured to be 150°. The obtained polyamide 6 / silica composite fiber with a functional powder content of 10% had a linear density of 60 dtex, a breaking strength of 4.5 cN / dtex, a breaking elongation of 30%, and a thermal conductivity of 0.0380 W / (m·K).
[0065] Example 4
[0066] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0067] (1) Weigh 50 g of nano-silicon dioxide powder with a particle size of 100 nm and 6 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 500°C for 5 hours. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-silicon dioxide powder.
[0068] (2) Add hydroxyl-activated nano-silica powder and 2.5 g of concentrated sulfuric acid to 400 g of undecanol, stir to fully disperse the nano-silica powder in the undecanol, then heat to 70° C., react for 7 hours, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0069] A polyester functional fiber, the preparation method of which comprises the following steps:
[0070] (1) 50 g of modified nano-silicon dioxide powder, 2440 g of polyester (PET) chips, 7.5 g of zinc stearate and 2.5 g of antioxidant 1076 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain polyester chips with a silica content of 2%.
[0071] (2) Polyester functional fibers with a silica content of 2% were produced by direct melt spinning.
[0072] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 21°, and the contact angle of the nano-silica sample after modification was measured to be 141°. The obtained polyester / silica functional fiber with a functional powder content of 2% had a linear density of 55 dtex, a breaking strength of 4.0 cN / dtex, a breaking elongation of 32%, and a thermal conductivity of 0.0630 W / (m·K).
[0073] Example 5
[0074] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0075] (1) Weigh 50 g of nano-silicon dioxide powder with a particle size of 500 nm and 8 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 400°C for 5 hours. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-silicon dioxide powder.
[0076] (2) Add hydroxyl-activated nano-silica powder and 1.5 g of p-toluenesulfonic acid to 200 g of octanol, stir to fully disperse the nano-silica powder in the octanol, then heat to 120° C., react for 2 h, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0077] A polyamide 6 functional fiber, the preparation method of which comprises the following steps:
[0078] (1) 50 g of modified nano-silica powder, 4930 g of polyamide 6 chips, 15 g of EBS and 5 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain polyamide 6 chips with a silica content of 1%.
[0079] (2) Polyamide 6 functional fibers with a silica content of 1% were produced by direct melt spinning.
[0080] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 25°, and the contact angle of the nano-silica sample after modification was measured to be 128°. The obtained polyamide 6 / silica functional fiber with a functional powder content of 1% had a linear density of 57 dtex, a breaking strength of 4.5 cN / dtex, a breaking elongation of 58%, and a thermal conductivity of 0.0702 W / (m·K).
[0081] Example 6
[0082] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0083] (1) Weigh 50 g of nano-silicon dioxide powder with a particle size of 250 nm and 5 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 550°C for 2 hours. After cooling naturally, wash them repeatedly with deionized water, centrifuge, and dry them to obtain hydroxyl-activated nano-silicon dioxide powder.
[0084] (2) Add hydroxyl-activated nano-silica powder and 1.0 g of dodecylbenzene sulfonic acid to 200 g of tetradecanol, stir to fully disperse the nano-silica powder in the tetradecanol, then heat to 80° C., react for 4 hours, centrifuge, wash, and dry to obtain modified nano-silica powder.
[0085] A polypropylene functional fiber, the preparation method of which comprises the following steps:
[0086] (1) 50 g of modified nano-silica powder, 444.5 g of polypropylene chips, 5 g of zinc stearate and 0.5 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polypropylene functional masterbatch with a silica content of 10%.
[0087] (2) A polypropylene functional masterbatch with a silica content of 10% is mixed with polypropylene chips and melt-spun to obtain a polypropylene functional fiber with a silica content of 5%.
[0088] The contact angle of the nano-silica sample before modification in this embodiment was measured to be 16°, and the contact angle of the nano-silica sample after modification was measured to be 119°. The obtained functional powder content of 5% polypropylene / silica functional fiber has a linear density of 65 dtex, a breaking strength of 3.5 cN / dtex, a breaking elongation of 28%, and a thermal conductivity of 0.0453 W / (m·K).
[0089] Example 7
[0090] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0091] (1) Weigh 150 g of nano-titanium dioxide powder with a particle size of 50 nm and 10 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 500°C for 2.5 hours. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-titanium dioxide powder.
[0092] (2) Add hydroxyl-activated nano-titanium dioxide powder and 7.5 g of p-toluenesulfonic acid to 975 g of tridecanol, stir to fully disperse the nano-titanium dioxide powder in the tridecanol, then heat to 100° C., react for 4 hours, centrifuge, wash, and dry to obtain modified nano-titanium dioxide powder.
[0093] A polyester functional fiber, the preparation method of which comprises the following steps:
[0094] (1) 150 g of modified nano titanium dioxide powder, 830 g of polyester (PET) chips, 15 g of zinc stearate and 5 g of antioxidant 1076 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyester functional masterbatch with a titanium dioxide content of 15%.
[0095] (2) A polyester functional masterbatch with a titanium dioxide content of 15% is mixed with polyester (PET) chips and melt-spun to obtain a polyester functional fiber with a titanium dioxide content of 7%.
[0096] The contact angle of the nano titanium dioxide silicon sample before modification in this embodiment was measured to be 14°, and the contact angle of the nano titanium dioxide sample after modification was measured to be 135° (as shown in FIG. Figure 2 The obtained polyester / titanium dioxide functional fiber with a functional powder content of 7% has a linear density of 62 dtex, a breaking strength of 4.0 cN / dtex, a breaking elongation of 31%, and a UPF value of 478.
[0097] Example 8
[0098] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0099] (1) Weigh 100 g of nano-titanium dioxide powder with a particle size of 25 nm and 13 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 600°C for 2 h. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-titanium dioxide powder.
[0100] (2) Add hydroxyl-activated nano-titanium dioxide powder and 4 g of dodecylbenzene sulfonic acid to 500 g of octanol, stir to fully disperse the nano-titanium dioxide powder in the octanol, then heat to 110° C., react for 5 h, centrifuge, wash, and dry to obtain modified nano-titanium dioxide powder.
[0101] A polyamide 6 functional fiber, the preparation method of which comprises the following steps:
[0102] (1) 100 g of modified nano-titanium dioxide powder, 1888 g of polyamide 6 chips, 10 g of EBS and 2 g of antioxidant 1010 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain polyamide 6 chips with a titanium dioxide content of 5%.
[0103] (2) Polyamide 6 functional fibers with a titanium dioxide content of 5% were produced by direct melt spinning.
[0104] The contact angle of the nano titanium dioxide sample before modification in this embodiment was measured to be 7°, and the contact angle of the nano titanium dioxide sample after modification was measured to be 120°. The obtained polyamide 6 / titanium dioxide functional fiber with a functional powder content of 5% had a linear density of 50 dtex, a breaking strength of 4.4 cN / dtex, a breaking elongation of 40%, and a UPF value of 392.
[0105] Example 9
[0106] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0107] (1) Weigh 60 g of nano-tourmaline powder with a particle size of 100 nm and 6 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 600°C for 2 h. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano-tourmaline powder.
[0108] (2) Add hydroxyl-activated nano-tourmaline powder and 2.5 g of p-toluenesulfonic acid to 375 g of tridecanol, stir to fully disperse the nano-tourmaline powder in the tridecanol, then heat to 90° C., react for 2.5 hours, centrifuge, wash, and dry to obtain modified nano-tourmaline powder.
[0109] A polyester functional fiber, the preparation method of which comprises the following steps:
[0110] (1) 60 g of modified nano-tourmaline powder, 532.2 g of polyester (PET) chips, 6 g of zinc stearate and 1.8 g of antioxidant 1076 were added into a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyester functional masterbatch with a tourmaline content of 10%.
[0111] (2) A polyester functional masterbatch with a tourmaline content of 10% is mixed with polyester (PET) chips and melt-spun to obtain a polyester functional fiber with a tourmaline content of 3%.
[0112] like Figure 3 Shown are scanning electron microscope (SEM) images of nano-tourmaline powder before and after modification of Example 9. In the figure, (a) is an SEM image of unmodified nano-tourmaline powder, and (b) is an SEM image of modified nano-tourmaline powder. It can be seen from the figure that the nano-inorganic powder is easy to agglomerate before modification, and after the surface hydrophobic modification, the agglomeration is reduced and the dispersibility is good.
[0113] The contact angle of the nano-tourmaline sample before modification in this embodiment was measured to be 15°, and the contact angle of the nano-tourmaline sample after modification was measured to be 139°. The functional powder content of the prepared polyester / tourmaline functional fiber was 3% and the linear density was 55 dtex, the breaking strength was 3.3 cN / dtex, the breaking elongation was 30%, and the negative oxygen ion release was 2740 / cm 3 .
[0114] Example 10
[0115] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0116] (1) Weigh 40 g of nano zirconium carbide powder with a particle size of 50 nm and 8 g of boric acid into a clean crucible, mix the two evenly, and then put them into a high-temperature furnace to react at 550° C. for 4 h. After natural cooling, wash repeatedly with deionized water, centrifuge, and dry to obtain hydroxyl-activated nano zirconium carbide powder.
[0117] (2) Add hydroxyl-activated nano zirconium carbide powder and 2 g of p-toluenesulfonic acid to 250 g of tridecanol, stir to fully disperse the nano zirconium carbide powder in the tridecanol, then heat to 90° C., react for 3 h, centrifuge, wash, and dry to obtain modified nano zirconium carbide powder.
[0118] A polyester functional fiber, the preparation method of which comprises the following steps:
[0119] (1) 40 g of modified nano zirconium carbide powder, 753.6 g of polyester (PET) chips, 4 g of zinc stearate and 2.4 g of antioxidant 1076 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyester functional masterbatch with a zirconium carbide content of 5%.
[0120] (2) A polyester functional masterbatch with a zirconium carbide content of 5% is mixed with polyester (PET) chips and melt-spun to obtain a polyester functional fiber with a zirconium carbide content of 1.5%.
[0121] The contact angle of the nano zirconium carbide sample before modification in this embodiment was measured to be 33°, and the contact angle of the nano zirconium carbide sample after modification was measured to be 130°. The obtained polyester / zirconium carbide functional fiber with a functional powder content of 1.5% had a linear density of 50 dtex, a breaking strength of 3.5 cN / dtex, an elongation at break of 30%, and a maximum temperature rise value of 7.5°C for light heat storage performance.
[0122] Embodiment 11
[0123] A surface hydrophobic modified nano inorganic powder, the preparation method of which comprises the following steps:
[0124] (1) Weigh 50 g of nano zinc oxide powder with a particle size of 40 nm and 5 g of boric acid into a clean crucible, mix them evenly, and then put them into a high-temperature furnace to react at 400°C for 5 hours. After natural cooling, wash them repeatedly with deionized water, centrifuge, and dry them to obtain hydroxyl-activated nano zinc oxide powder.
[0125] (2) Add hydroxyl-activated nano zinc oxide powder and 1.4 g p-toluenesulfonic acid to 250 g of undecanol, stir to fully disperse the nano zinc oxide powder in the undecanol, then heat to 140° C., react for 3 h, centrifuge, wash, and dry to obtain modified nano zinc oxide powder.
[0126] A polyester functional fiber, the preparation method of which comprises the following steps:
[0127] (1) 50 g of modified nano zinc oxide powder, 442.5 g of polyester (PET) chips, 5 g of zinc stearate and 2.5 g of antioxidant 1076 were added to a mixer, and after being fully mixed, they were transferred to a screw extruder for melt extrusion to obtain a polyester functional masterbatch with a zinc oxide content of 10%.
[0128] (2) A polyester functional masterbatch with a zinc oxide content of 10% is mixed with polyester (PET) chips and melt-spun to obtain a polyester functional fiber with a zinc oxide content of 5%.
[0129] The contact angle of the nano zinc oxide sample before modification in this embodiment was measured to be 20°, and the contact angle of the nano zinc oxide sample after modification was measured to be 124°. The obtained polyester / zinc oxide functional fiber with a functional powder content of 5% had a linear density of 48 dtex, a breaking strength of 3.2 cN / dtex, an elongation at break of 27%, and an antibacterial rate of more than 99% against Staphylococcus aureus and Escherichia coli.
[0130] The method for preparing modified nano inorganic powder of the present invention is simple and has mild reaction conditions. No toxic organic reagent is used as a solvent. The modifier can also be recycled. The prepared modified nano inorganic powder has good hydrophobicity. The inorganic powder is evenly dispersed in the prepared functional masterbatch and functional fiber, which can effectively solve the problem of poor dispersibility and easy agglomeration in organic polymers.
[0131] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing surface hydrophobic modified nano inorganic powder, characterized in that: The following steps are involved: S1: heating the nano inorganic powder and boric acid to react to obtain hydroxyl activated nano inorganic powder; S2: reacting the hydroxyl-activated nano-inorganic powder with a long carbon chain alkanol to obtain a surface hydrophobic-modified nano-inorganic powder.
2. The method for preparing surface hydrophobic modified nano inorganic powder according to claim 1, characterized in that: In step S1, the nano inorganic powder is selected from one or more of nano silicon dioxide, nano titanium dioxide, nano tourmaline, nano zirconium carbide or nano zinc oxide; the particle size of the nano inorganic powder is 10 to 500 nm, and the mass ratio of the nano inorganic powder to boric acid is 5 to 15:
1.
3. The method for preparing surface hydrophobic modified nano inorganic powder according to claim 1, characterized in that: In step S1, in the heating reaction, the reaction temperature is 400-600° C. and the reaction time is 2-5 hours.
4. The method for preparing surface hydrophobic modified nano inorganic powder according to claim 1, characterized in that: In step S2, the molecular formula of the long carbon chain alkanol is CH3(CH2) n OH, wherein n=8-14, and the mass ratio of the nano inorganic powder to the long carbon chain alkanol is 1:4-8.
5. The method for preparing surface hydrophobic modified nano inorganic powder according to claim 1, characterized in that: In step S2, in the reaction, the catalyst is one or more of concentrated sulfuric acid, dodecylbenzenesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid.
6. The method for preparing surface hydrophobic modified nano inorganic powder according to claim 1, characterized in that: In step S2, during the reaction, the reaction temperature is 70-150° C. and the reaction time is 2-7 hours.
7. A method for preparing a functional fiber, characterized in that: include: The surface hydrophobic modified nano inorganic powder, polymer slices, dispersant and antioxidant are melt-blended and extruded to obtain functional masterbatch, and the functional fiber is obtained by melt spinning; The surface hydrophobic modified nano inorganic powder is prepared by the method according to any one of claims 1 to 6.
8. The method for preparing functional fiber according to claim 7, characterized in that: The polymer slice is selected from one of polyethylene terephthalate slice, polyamide slice and polypropylene slice; The dispersant is vinyl bisstearamide or zinc stearate, and the mass content in the functional masterbatch is 0.3-3%; The antioxidant is antioxidant 1010 or antioxidant 1076, and its mass content in the functional masterbatch is 0.01-0.5%; The mass content of the surface hydrophobic modified nano inorganic powder in the functional masterbatch is 1-30%.
9. The method for preparing functional fiber according to claim 7, characterized in that: The mass content of the surface hydrophobic modified nano inorganic powder in the functional fiber is 1-10%.
10. The method for preparing functional fiber according to claim 7, characterized in that: The melt spinning comprises: directly melt spinning the functional masterbatch or mixing it with additional polymer chips and then adding it into a melt spinning machine for spinning.
Citation Information
Patent Citations
Preparation method of functional polyester fibers
CN102719932A
Method of preparing super-hydrophobic coating by compounding waterborne polyurethane and hydrophobic modified inorganic nanoparticles
CN109370408A
Thermal insulation material and high-permeability hydrophobic modification method thereof
CN115465868A
Modified nano silicon dioxide-reactive polyurethane cross-linked water repellent agent and preparation method thereof
CN115852703A
Hydrophobic polyester fiber as well as preparation method and application thereof
CN116770452A
Cited By
Twelve-hole far infrared heating fiber and preparation method thereof
CN120738790A
Light-absorbing and heating jacket fabric with high wear resistance as well as preparation method and application of light-absorbing and heating jacket fabric
CN120797238A